2015
DOI: 10.1016/j.jcf.2014.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Foundation and European Cystic Fibrosis Society Survey of cystic fibrosis mental health care delivery

Abstract: These data have informed the decision-making, dissemination and implementation strategies of the Mental Health Guidelines Committee sponsored by the CFF and ECFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…People with CF are able to set and achieve major life milestones including education, marriage, and having children. Mental health issues including depression and anxiety are common (Abbott et al 2015). Despite advances in the outlook for affected individuals, there is still no known cure for the condition.…”
Section: Treatment and Disease Managementmentioning
confidence: 99%
“…People with CF are able to set and achieve major life milestones including education, marriage, and having children. Mental health issues including depression and anxiety are common (Abbott et al 2015). Despite advances in the outlook for affected individuals, there is still no known cure for the condition.…”
Section: Treatment and Disease Managementmentioning
confidence: 99%
“…The prevalence of depression and anxiety is high in patients with CF as well as their caregivers; thus, screening, interventions, pharmacologic treatment, and future research in this area should be prioritized. A survey showed that mental health screening was supported in US and European CF Centers, but was inadequate and highly variable, underscoring the need for standardized instruments and attention to barriers in implementation . The International Committee on Mental Health in CF published a consensus statement for screening and treating depression and anxiety.…”
Section: Multi‐system Comorbiditiesmentioning
confidence: 99%
“…A survey showed that mental health screening was supported in US and European CF Centers, but was inadequate and highly variable, underscoring the need for standardized instruments and attention to barriers in implementation. 48 The International Committee on Mental Health in CF published a consensus statement for screening and treating depression and anxiety. Highlights include education and supportive measures toward prevention, minimization of distress with medical procedures, and screening of patients and caregivers with referral for evidence-based psychological interventions, exposurebased cognitive behavioral therapy, or consideration of antidepressants.…”
Section: Mental Healthmentioning
confidence: 99%
“…A recent survey of CF providers across Europe and the USA indicated that at least 48 different screening measures of psychological distress are in use. 7 Thus, standardisation of this assessment process is needed.…”
Section: Dear Editorsmentioning
confidence: 99%